HDAC1 dysregulation induces aberrant cell cycle and DNA damage in progress of TDP‐43 proteinopathies - Cheng‐Chun Wu; Lee‐Way Jin; I‐Fang Wang; Wei‐Yen Wei; Pei‐Chuan Ho; Yu‐Chih Liu; Kuen‐Jer Tsai (EMBO Molecular Medicine)
Abstract TAR DNA‐binding protein 43 (TDP‐43) has been implicated in frontotemporal lobar degeneration with ubiquitin‐positive inclusions (FTLD‐TDP) and amyotrophic lateral sclerosis. Histone deacetylase 1 (HDAC1) is involved in DNA repair and neuroprotection in numerous neurodegenerative diseases. However, the pathological mechanisms of FTLD‐TDP underlying TDP‐43 proteinopathies are unclear, and the role of HDAC1 is also poorly understood. Here, we found that aberrant cell cycle activity and DNA damage are important pathogenic factors in FTLD‐TDP transgenic (Tg) mice, and we further identified these pathological features in the frontal cortices of patients with FTLD‐TDP. TDP‐43 proteinopathies contributed to pathogenesis by inducing cytosolic mislocalization of HDAC1 and reducing its activity. Pharmacological recovery of HDAC1 activity in FTLD‐TDP Tg mice ameliorated their cognitive and motor impairments, normalized their aberrant cell cycle activity, and attenuated their DNA damage and neuronal loss. Thus, HDAC1 deregulation is involved in the pathogenesis of TDP‐43 proteinopathies, and HDAC1 is a potential target for therapeutic interventions in FTLD‐TDP.